1979
DOI: 10.1038/bjc.1979.260
|View full text |Cite
|
Sign up to set email alerts
|

Variation of melanoma incidence with latitude in North America and Europe

Abstract: Summary.-The relationship between melanoma incidence and latitude was investigated in North America and Europe, using the data collected by 43 population-based cancer registries. In North America melanoma incidence increased with decreasing latitude, supporting the role of UV light in the induction of melanoma. Within England the data from the National Cancer Registration scheme also showed the trend of increased frequency of melanoma with decreasing latitude. In contrast, across Europe the trend was in the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 11 publications
3
39
0
1
Order By: Relevance
“…While these countries are at high latitudes, a north-south gradient of incidence rates has been observed, even among the northernmost Scandinavian nations (9,52,53). Similar observations have been made among Caucasian populations in the United States (54,55), New Zealand (56), and other nations (48).…”
Section: Geographysupporting
confidence: 58%
See 1 more Smart Citation
“…While these countries are at high latitudes, a north-south gradient of incidence rates has been observed, even among the northernmost Scandinavian nations (9,52,53). Similar observations have been made among Caucasian populations in the United States (54,55), New Zealand (56), and other nations (48).…”
Section: Geographysupporting
confidence: 58%
“…Incidence of melanoma varies by geographic location among people of the same ethnicity (47)(48)(49)(50). Differences in geography can translate to differences in atmospheric absorption, latitude, altitude, cloud cover, and season-all variables that influence incident UV radiation.…”
Section: Geographymentioning
confidence: 99%
“…The exces male incidence at this site shown in Table I Europe (20). It was previously shown that the trend of melanoma incidence with latitude differed between these two continents: an increase with decreasing latitutde in North America, and the converse in Europe (Crombie, 1979a). However, both continents show the same pattern of sex differences in incidence: male higher on head and remainder (trunk) and female higher on the upper and lower limbs ( Table I).…”
Section: Reliability Of the Datamentioning
confidence: 82%
“…Firstly, the incidence and mortality from melanoma has been found to increase with proximity to the equator in Australia, North America, England and Wales, Norway and Sweden (Lancaster, 1956;Haenszel, 1963;Magnus, 1973;Elwood et al, 1974;Eklund & Malec, 1978;Crombie, 1979a).…”
mentioning
confidence: 99%
“…Epidemiological studies have implicated sunlight exposure as a major factor in melanoma development [3]. Furthermore, Caucasians have an increased risk of melanoma in sun-exposed areas relative to Blacks [4]. A hereditary component seems to exist in 5-10% of the individuals with melanoma [5].…”
Section: Introductionmentioning
confidence: 99%